Policy-Driven Adaptation of Protocol Stacks - Rosa, Liliana (2009)
Today's mobile applications need to execute in a wide range of heterogeneous devices, that operate in different conditions. In this context, dynamic adaptation of the underlying communication support is fundamental to achieve adequate performance. We address the problem of supporting dynamic adaptation of communication protocol stacks through a policy-oriented approach, which promotes the separation of adaptation from protocol logic. In this paper, we provide an approach overview, and focus on the policy language and modeling primitives that allow to capture the adaptation requirements identified from the experience with Appia framework